STUDI KUALITAS AIR PARAMETER FISIKA DAN KIMIA DI PERAIRAN SUNGAI SESAYAP KABUPATEN TANA TIDUNG - Weliyadi, Encik; Irawati, Heni; Anzar, Radifah (Jurnal Borneo Saintek, 2023)
The diversity of human activities along the river causes pollution to the river is increasing, one of which is domestic waste disposal. A river is a place of waste disposal from various land activities. The purpose of this study was to determine the condition of water quality from the physical and chemical parameters in the Sesayap River, Tana Tidung Regency. The research method used is descriptive quantitative. The results showed that the condition of river water quality in the Tideng Pale Village is temperature ranged between 25-32 oC, salinity 7-15 ppt, turbidity 1.15-4.43 mg/L, water transparency 95-125 mg/L, pH 7.2- 7.7, phosphate 0.006-0.063 mg/L, ammonia 0.038-0.449 mg/L, nitrate 0.22 to 0.28 mg/L, DO 3.10-4.52 mg/L, BOD 1.12-2.17 mg/L. River water quality in the Sesayap Village is temperature ranged between 20-30 oC, salinity 8-15 ppt, turbidity 1.99-3.75 NTU, water transparency 100-135 cm, pH 6.2-7.4, phosphate 0.025-0.038 mg/L, ammonia 0.063-0.409 mg/L, nitrates 0.23-0.26 mg/L, DO 3.25-4.57 mg/L, BOD 1.23-2.23 mg/L, whereas river water quality in Bebatu Village the temperature parameters range from 22-36 oC, salinity 10-25 ppt, turbidity 2.13-4.19 NTU, water transparency 110-130 cm, pH 6-7.8, phosphate 0.010 to 0.30 mg/L, ammonia 0.065-0.525 mg/L, nitrates 0.26-0.30 mg/L, DO 3.10-4.60 mg/L, BOD 1.17-2.23 mg/L. The conclusion of this study is that the condition of water quality is still relatively good.